Elastic Electron Scattering From Unstable Neutron-Rich P19PC Exotic Nucleus - Radhi, R.; Hamoudi, A.; Ridha, A. (Iraqi Journal of Science, 2024)
The ground state proton, neutron, and matter density distributions and corresponding root-mean-square (rms) of P19PC exotic nucleus are studied in terms of two-frequency shell model (TFSM) approach. The single-particle wave functions of harmonic-oscillator (HO) potential are used with two different oscillator parameters bRcoreR and bRhaloR. According to this model, the core nucleons of P18PC nucleus are assumed to move in the model space of spsdpf. The shell model calculations are carried out for core nucleons with w)20(+ truncations using the realistic WBPinteraction. The outer (halo) neutron in P19PC is assumed to move in the pure 2sR1/2R-orbit. The halo structure in P19PC is confirmed with 2sR1/2R-dominant configuration.Elastic electron scattering form factor of P19PC nucleus is also investigated by meansof the Plane Wave Born approximation. The effect of the long tail behavior (foundin the calculated matter density distribution) on the elastic form factor of P19PC isstudied. The calculated matter densities and form factors of stable P13PC and unstableP19PC are compared. It is found that the difference between the nucleon form factors ofP13PC and P19PC nuclei is attributed to the difference presented in the matter densities ofthese nuclei. Hence the difference in the matter densities of P19PC and P13PC nucleimainly comes from the neutron skin of the core P18PC and from the difference in theneutron density distribution of the last one neutron in both P19PC and P13PC nuclei. It isfound that elastic electron scattering from exotic nuclei can provide predictions forthe near future experiments on the electron-radioactive beam colliders where theeffect of the neutron halo or skin on the charge distributions is planned to be studied.PACS number(s): 25.60.Dz, 21.10.Gv, 27.30.+t, 13.14.Gp.